THE EFFECT OF SMARTPHONE-BASED VIDEO MEDIA IN SCIENCE AND SCIENCE LEARNING USING EXPERIMENTAL METHODS ON THE LEARNING INTERESTS OF ELEMENTARY SCHOOL STUDENTS - Yusdin Gagaramusu; Azizah; Asriani; Raodatul Jannah (Jurnal Cakrawala Pendas, 2025)
The purpose of this study is to determine the Effect of the Use of Smartphone-Based Video Media in IPAS Learning on the Learning Interest of Elementary School Students. This study used a quantitative quasi-experimental design with a type of Non-equivalent Control Group which involved two classes given different treatments, namely the experimental group and the control group. The subjects of this study are 56 students of class IV A & Class IV B B SDN 22 Palu. Data collection was carried out using research instruments in the form of questionnaires, observations and interviews. Data analysis used hypothesis tests through paired test samples t-test and prerequisite tests, namely normality tests and homogeneity tests assisted by the SPSS Statistics version 27 program. Based on the results of this study, it shows that the significance of 0.001 < 0.05 is accepted, so the hypothesis Ha is accepted and Ho is rejected, thus the Use of Smartphone-Based Video Media in Social Science Learning using the Experimental Method has an effect in increasing the learning interest of elementary school students.